Utilization and Management of Marine Resources in the Coastal Area Based On Regional Autonomy - Uktolseja, Novyta (Faculty of Law, Universitas Pattimura, 2022)
Introduction: In the current development planning efforts, the management of small islands faces various threats, both from the ecological aspect as well as from the social aspect.Purposes of the Research: This study aims to examine and analyze strategies and policies for the utilization and management of marine resources in the Coastal Area of the Aru Islands Regency, as well as the obstacles to the utilization and management of marine resources in the Coastal Area of the Aru Islands Regency.Methods of the Research: This study uses the sociolegal method with primary data and secondary data analyzed descriptively. This research is directed to be able to study and analyze the utilization and management of marine resources in the Coastal Area of the Aru Islands Regency.Results of the Research: There are several strategies carried out by the local government through the Fisheries and Marine Service of the Aru Islands Regency, namely providing assistance to the community, collaboration with the Ministry of Maritime Affairs and Fisheries, as well as the Aru Islands Regency Regional Government in improving facilities and infrastructure, especially in the fisheries and marine sector, quality improvement human resources through training in the field of fisheries, as well as collaboration with the Ministry of Maritime Affairs and Fisheries to provide scholarships for fishermen's children to study and study at educational institutions under the auspices of the ministry of fisheries. Obstacles in implementing the utilization and management of the abundant marine resource potential in the Aru Islands are limited facilities and infrastructure to manage and utilize the potential of marine resources owned, weak market share, still controlled by strong investors (market monopoly) by strong investors, so that the community is not able to compete, the quality of human resources both local governments and the community in terms of managing and utilizing marine resources owned is also very low, there is still a lack of assistance from the government and the Department of Marine Affairs and Fisheries so that the management and utilization of marine resources is still not optimal, The difficulty of Vulnerability of control on the outermost small islands of the Aru Islands.